Comparison of hyper-cross-linked polystyrene/polyacryldiethylenetriamine (HCP/PADETA) interpenetrating polymer networks (IPNs) with hyper-cross-linked polystyrene (HCP): structure, adsorption and separation properties. Issue 38 (1st April 2016) - Fu, Zhenyu; Han, Shan; Huang, Jianhan; Liu, You-Nian
Abstract : HCP/PADETA IPNs can separate salicylic acid efficiently from phenol in a mixed solution. Abstract : Novel hyper-cross-linked polystyrene/polyacryldiethylenetriamine (HCP/PADETA) interpenetrating polymer networks (IPNs) were prepared, characterized and evaluated for their adsorption and separation properties using hyper-cross-linked polystyrene (HCP) as the reference. In spite of its much lower Brunauer–Emmett–Teller surface area and less pore volume, HCP/PADETA IPNs possessed a preferable pore structure and appropriate polarity, resulting in a larger equilibrium capacity, faster adsorption rate, higher dynamic breakthrough and saturated capacity towards salicylic acid than HCP. In particular, HCP/PADETA IPNs had a higher enrichment factor for salicylic acid over phenol, leading to the high-efficiency separation of salicylic acid from phenol in their mixed solution.